Testosterone metabolism in the human endometrium: A combination of metabolic (mass spectrometry) and enzyme expression (RT-PCR). - Angela Elizabeth Taylor (2009)
Localised steroid metabolism is important in proliferative disorders of theendometrium. The metabolism of testosterone, an important precursor inendometrial disorders, was investigated by mass spectrometry and RT-PCR (realtime polymerase chain reaction), allowing determination of steroid metabolites andexpression of steroid converting enzymes; aromatase, 17P-HSD1, 2, 4, 5, 7, 8,(hydroxysteroid dehydrogenase) and 5AR1, 2 (alpha reductase). Samples werederived from cell lines (Ishikawa, HEC-1A, HEC-1B, RL95-2, COV434), andbiopsies; fertile, endometriosis, poly-cystic ovary syndrome (PCOS), endometrialhyperplasia, unexplained infertility, endometrial polyp.Optimum mass spectrometry techniques, determined using steroid standards, wereLC/MS for androgens and LC/MS/MS for oestrogens, following dansyl-chloridederivatisation. GC/MS was less sensitive.The route of testosterone metabolism varied in the cell lines and clinical biopsies, themajor metabolite was correlated with high expression of 5AR1 or 17p-HSD2, 4 and8. If DHT (dihydrotestosterone) was produced high basal expression of 5AR1 wasobserved and if androstenedione was produced high basal expression of HSD2, 4 or8 was observed. A mixture of DHT and androstenedione was correlated withexpression of 5AR1 and 17P-HSD2, 4 or HSD8.Changes in enzyme expression were correlated with changes in steroid concentrationafter testosterone treatment, as follows:1. Increased 5AR1 expression was correlated with increased DHT concentrationin Ishikawa, HEC-1B, COV434, PCOS, endometriosis, stromal hyperplasiaand ovarian cyst biopsies.2. Increased expression of 5AR2 was correlated with increased androsteroneconcentration in fertile and unexplained infertility biopsies.3. Increased 17p-HSD5 expression was correlated with increased testosteroneconcentration in HEC-1A cells.4. Increased aromatase expression was correlated to increased oestradiol andoestrone concentrations in a hyperplasia biopsy.Analysis of a range of enzymes and steroids produced testosterone metabolism mapsof the endometrium (and associated disorders) highlighting steroids which couldcontribute to endometrial disorders and viable enzyme target(s) for inhibition (5AR1,17P-HSD2, 4, 8).